Waste water as irrigation alternative in two bean cultivars - De Melo, Mara Rubia Mendes [UNESP]; De Sousa, Francielly Guieiro Gomes [UNESP]; De Carvalho, Renata Da Silva Cuba [UNESP]; Grassi Filho, Hélio [UNESP]; Klar, Antonio Evaldo [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2020)
The objective was to study the effect of water deficit in two bean cultivars (Phaseolus vulgaris L.), in the vegetative and reproductive phases, associated with the use of reuse water, using a 2x2x3 factorial scheme. Three factors were evaluated: 1) the use of two types of water for irrigation-potable (P) and waste (R), 2) two bean cultivars (emperor IAC (C1) and Dama TAA (C2)) and 3) the water regimes employed, a) Control: keeping the soil in the field capacity, whose value was-10kPa, b) Stress 1: with water deficiency in the vegetative phase; c) Stress 2: water deficiency in the reproductive phase. Growth and biomass evaluations were made. Triple interaction of the factors occurred only for the variable plant height. The three factors separately interfered with the development of common bean, especially at the end of the cycle. Water stress in the vegetative and reproductive phases influenced practically all evaluations, interfering negatively with the development of the crop. For the cultivars, there were also differences in growth and plant biomass traits. Regarding the water factor, there was an effect on the parameters height and mass of dry matter, and the drinking water provided values higher than those obtained with wastewater.
Água residuária como alternativa de irrigação em duas cultivares de feijão
Keywords: Irrigation; Phaseolus vulgaris L.; Reuse water; Water deficit